Predicting mortality during long-term follow-up in pulmonary arterial hypertension. Issue 2 (31st May 2021) - Kylhammar, David; Hjalmarsson, Clara; Hesselstrand, Roger; Jansson, Kjell; Kavianipour, Mohammad; Kjellström, Barbro; Nisell, Magnus; Söderberg, Stefan; Rådegran, Göran
The European Society of Cardiology (ESC) and European Respiratory Society (ERS) guideline recommendation of comprehensive risk assessments, which classify patients with pulmonary arterial hypertension (PAH) as having low, intermediate or high mortality risk, has not been evaluated during long-term follow-up in a "real-life" clinical setting. We therefore aimed to investigate the utility of risk assessment in a clinical setting for up to 5 years post diagnosis. 386 patients with PAH from the Swedish PAH Registry were included. Risk group (low/intermediate/high) and proportion of low-risk variables were investigated at 3-, 4- and 5-year follow-ups after time of diagnosis. In an exploratory analysis, survival rates of patients with low-intermediate or high-intermediate risk scores were compared. A low-risk profile was in multivariate Cox proportional hazards regressions found to be a strong, independent predictor of longer transplant-free survival (p<0.001) at the 3-, 4- and 5-year follow-ups. Also, for the 3-, 4- and 5-year follow-ups, survival rates significantly differed (p<0.001) between the three risk groups. Patients with a greater proportion of low-risk variables had better (p<0.001) survival rates. Patients with a high-intermediate risk score had worse survival rates (p<0.001) than those with a low-intermediate risk score. Results were similar when excluding patients with ≥3 risk factors for heart failure with preserved ejection fraction, atrial fibrillation and/or age >75 years at diagnosis. Our findings suggest that the ESC/ERS guideline strategy for comprehensive risk assessments in PAH is valid also during long-term follow-up in a "real-life" clinical setting. ESC/ERS guidelines' risk stratification table successfully predicts outcome during long-term follow-up in pulmonary arterial hypertension https://bit.ly/3nXJbop